Ausbildungsmarkt unter Druck: die aktuelle Entwicklung und deren Antworten darauf; Training market under pressure: What are the current developments and their responses? - Andreas Lagemann; Jan Wedemeier (Wirtschaftsdienst, 2022)
– The number of new apprenticeship training contracts has been declining for years. The decline can be explained by a variety of factors. It can initially be assumed that the economic development due to the COVID-19 pandemic and the associated loss of training places offer an explanation. However, the trend is of a longer nature. This article examines proposed solutions, such as the training fund allocation that is currently in discussion, seem more like an expression of futile politics.
Keywords: J21; J6; R1; 330; Ausbildungsmarkt; Auszubildende; Deutschland